Implementation of Simple Additive Weighting (SAW) Method For Selecting a Tutoring Center - Lilis Indrayani; Yuliana Sangka (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Abstract Tutoring Institutions (Bimbel) are non-formal educational institutions that work to maximize children's learning potential which may not be fully achieved through conventional education. There are many bilingual educational institutions that exist today, each with its own regulations and requirements designed to attract students, especially elementary school (SD) students. Standards that are often used as a guide to attract students are Tuition fees, distance from home, facilities. and teaching staff. Alternatives to bimbel institutions are Zefanya Bimbel, Study Star Bimbel, Camat Bimbel and Quantum Bimbel. Each bimbel institution has different requirements or policies, it presents a unique challenge for students to choose atutoring place that suits their expectations. One of the methods of problem solving that can be used is by building a computer-based system to help decision-making, the method used is the Simple Additive Weighting Method (SAW), The SAW method can select the best alternatives from several available alternatives because it is ranked after determining the weight of each feature. From this research, getting the results of Bimbel Camat becomes the recommendation of the best choice of bimbel. Keywords: Decision Support System, Simple Additive Weighting, Alternative